MAKNA TRANSFORMASI DIRI MENURUT AMSAL 1:7 DAN YOHANES 3:3-8 SERTA RELEVANSI DALAM KONSEP SELAMET - ORANG JAWA - Marianus Ivo Meidinata (Jurnal Teologi (Journal of Theology), 2022)
ABSTRACTIn this study, the author focuses on the meaning of Proverbs 1:7 and John 3:3-8 to find the Christian concept of transformation. This research is comparative research with a semantic analysis approach. This study concludes that Proverbs 1:7 about the fear of God and knowledge and John 3:3-8 about being born again in water and the Spirit contain meaning about the concept of transformation in Christianity. The effort of self-transformation or self-renewal is the fruit of a mature believer willing to respond to God's grace of love and unity. This gift of renewal is the gift of being a new human being, returning to being a child of God so that he is ready to become a messenger of God. The author finds that these meanings and concepts are relevant (harmonious and mutually enriching understanding) to Javanese beliefs about the concept of salvation as the goal of human life. The Christian transformation has a distinctive manifestation in Javanese culture through the culture of spiritual practice and sapa ingsun. This mysticism culture becomes richer when it is understood as a contemplation, living in the presence of God in daily activities. The fruit of this way of life is manunggaling kawula lan Gusti, in which God wants people who live in His Spirit to reunite with Him - the source of life. ABSTRAKDalam studi ini, penulis mengambil fokus pada pemaknaan Amsal 1:7 dan Yohanes 3:3-8 untuk menemukan konsep Kristiani mengenai transformasi. Penelitian ini merupakan penelitian komparatif dengan pendekatan analisis semantik. Studi ini sampai kepada kesimpulan bahwa Amsal 1:7 tentang takut akan Tuhan dan pengetahuan, serta Yohanes 3:3-8 tentang kelahiran kembali dalam air dan Roh mengandung makna mengenai konsep transformasi dalam Kristiani. Usaha transformasi diri atau membarui diri adalah buah dari kedewasaan seorang beriman yang bersedia menanggapi rahmat kasih dan persatuan dari Tuhan. Anugerah pembaruan ini adalah anugerah menjadi manusia baru, kembali menjadi anak Allah sehingga siap menjadi pewarta Tuhan. Penulis menemukan bahwa makna dan konsep ini relevan (selaras dan saling memperkaya pemahaman) dengan kepercayaan Jawa tentang konsep selamet sebagai tujuan hidup manusia. Transformasi Kristiani memiliki perwujudan khas dalam budaya Jawa melalui budaya olah batin dan sapa ingsun. Budaya kebatinan ini menjadi lebih kaya ketika dimengerti sebagai sebuah kontemplasi, hidup di hadirat Tuhan dalam aktivitas sehari-hari. Buah dari cara hidup ini adalah manunggaling kawula lan Gusti, yang mana Tuhan menghendaki supaya manusia yang hidup dalam Roh-Nya bersatu kembali dengan Dia - sumber kehidupan.